Mitochondrial Genome Analyses Suggest Multiple Trichuris Species in Humans, Baboons, and Pigs from Different Geographical Regions. - Mohamed B F Hawash; Lee O Andersen; Robin B Gasser; Christen Rune Stensvold; Peter Nejsum (Public Library of Science (PLoS), 2015)
BACKGROUND:The whipworms Trichuris trichiura and Trichuris suis are two parasitic nematodes of humans and pigs, respectively. Although whipworms in human and non-human primates historically have been referred to as T. trichiura, recent reports suggest that several Trichuris spp. are found in primates. METHODS AND FINDINGS:We sequenced and annotated complete mitochondrial genomes of Trichuris recovered from a human in Uganda, an olive baboon in the US, a hamadryas baboon in Denmark, and two pigs from Denmark and Uganda. Comparative analyses using other published mitochondrial genomes of Trichuris recovered from a human and a porcine host in China and from a françois' leaf-monkey (China) were performed, including phylogenetic analyses and pairwise genetic and amino acid distances. Genetic and protein distances between human Trichuris in Uganda and China were high (~19% and 15%, respectively) suggesting that they represented different species. Trichuris from the olive baboon in US was genetically related to human Trichuris in China, while the other from the hamadryas baboon in Denmark was nearly identical to human Trichuris from Uganda. Baboon-derived Trichuris was genetically distinct from Trichuris from françois' leaf monkey, suggesting multiple whipworm species circulating among non-human primates. The genetic and protein distances between pig Trichuris from Denmark and other regions were roughly 9% and 6%, respectively, while Chinese and Ugandan whipworms were more closely related. CONCLUSION AND SIGNIFICANCE:Our results indicate that Trichuris species infecting humans and pigs are phylogenetically distinct across geographical regions, which might have important implications for the implementation of suitable and effective control strategies in different regions. Moreover, we provide support for the hypothesis that Trichuris infecting primates represents a complex of cryptic species with some species being able to infect both humans and non-human primates.